Solvent-Free MgO-Functionalized Mesoporous Catalysts for Jatropha Oil Transesterification - Anamagreth Andrew; Jamidu Katima; Keat Teong Lee; James Epiphan Gabriel Mdoe (Journal of Nanotechnology)
A convenient solvent-free technique was employed in the functionalization of Micelle-Templated Silica using Cashew Nut Shell Liquid (MTS-CNSL) as a template and magnesium nitrate as a precursor salt. Magnesium oxide species was highly dispersed in MTS-CNSL by manually grinding the precursor salt and the as-synthesized mesoporous silica followed by calcination. The resultant modified mesoporous silicas MgO/MTS-CNSL were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR, N2 adsorption/desorption), and scanning electron microscopy/energy dispersive X-ray (SEM/EDX). MgO/MTS-CNSL (30) having small specific surface area of 16.7 m2/g and larger pore volume of 0.02 cm3/g, presented higher activity of 81.45% for jatropha oil under optimized conditions (200°C, 4 h, 36 : 1 methanol : oil ratio, 500 rpm, and 6% wt of catalyst). This method of catalyst development has an advantage of being highly energy- and time-efficient.